The FERRUM project: new experimental and theoretical f-values for 4p-4d transitions in FeII applied to HST spectra of chi Lupi - Nilsson, H; Sikstrom, C. M; Li, Z. S; Lundberg, Hans; Raassen, A. J. J; Johansson, S; Leckrone, D. S; Svanberg, Sune (Astronomy & Astrophysics, 2000)
Radiative lifetimes for six highly excited levels in Fe II have been measured at Lund Laser Centre applying the laser induced fluorescence technique and two-step excitation. The energy levels belong to the even-parity 3d(6)(D-5)(4)d subconfiguration at about 10 eV. Branching fractions (BF:s) of 29 transitions from these levels to the 3d(6)(D-5)4p subconfiguration at about 5 eV have been measured in the wavelength region 2000-3000 Angstrom with the Lund Fourier Transform Spectrometer. By normalizing the BF:s with the lifetimes we get experimental oscillator strengths for these 29 4p-4d lines. The oscillator strengths are compared with new theoretical calculations using the orthogonal operator technique and applied to high-resolution spectra of the star chi Lupi, recorded with the Hubble Space Telescope.